2021
DOI: 10.3390/ijerph18063252
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Severe Acute Respiratory Syndrome Coronavirus 2 on the Surfaces of Tourist-Recreational Facilities in Italy

Abstract: A Coronavirus disease (COVID-19), caused by a new virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), spreads via direct contact through droplets produced by infected individuals. The transmission of this virus can also occur via indirect contact if objects and surfaces are contaminated by secretions from individuals with COVID-19 or asymptomatic carriers. Environmental contamination with SARS-CoV-2 is high in hospital settings; on the contrary, surface contamination in non-healthcare se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
1
23
1
Order By: Relevance
“…As has been demonstrated in previous examples such as the 2013–2014 silent polio epidemic in Israel [ 40 ], environmental surveillance can be used as a tool to decide when to enact restrictions, with the aim of an early introduction and avoiding premature repeal [ 41 , 42 ]. This surveillance approach could also be used to inform vaccination distribution [ 43 ] and to investigate emerging genomic variants circulating in the population [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As has been demonstrated in previous examples such as the 2013–2014 silent polio epidemic in Israel [ 40 ], environmental surveillance can be used as a tool to decide when to enact restrictions, with the aim of an early introduction and avoiding premature repeal [ 41 , 42 ]. This surveillance approach could also be used to inform vaccination distribution [ 43 ] and to investigate emerging genomic variants circulating in the population [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The swabs were vortexed for 20 s and transferred to a new 15-mL tube under sterile conditions. We conducted molecular investigation for the presence of SARS-CoV-2 RNA using real-time reverse transcription-polymerase chain reaction (RT-PCR), as documented in the literature and our previous study [13,15]. Nucleic acid was extracted with 5 mL of NRS medium using the NucliSENS miniMAG semi-automatic extraction system with magnetic silica, according to the manufacturer's instructions (bioMerieux, Marcy-l'Etoile, Lyon, France).…”
Section: Molecular Analysismentioning
confidence: 99%
“…In Italy, SARS-CoV-2 RNA has been detected in molecular investigations of surfaces in tourist and recreational facilities, such as bathroom door handles, refrigerator handles, handrails, and bar counters [13]. Although molecular investigation can detect the viral genome, viability of the virus has not been demonstrated using these methods.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 transmission occurs primarily through respiratory routes, but transmission from contaminated surfaces, or fomites, has been a concern. SARS-CoV-2 RNA has been detected on surfaces in healthcare [1][2][3][4][5][6][7][8] and community [9,10] settings, residences [11], quarantine rooms [3,12], and a cruise ship [13]; however, attempts to culture virus from environmental samples testing positive for SARS-CoV-2 have not been successful [2,3,6,7,13]. Only studies examining the stability of SARS-CoV-2 on surfaces in controlled laboratory settings have found that viable virus can be recovered from plastic and stainless steel for 3-4 days [14,15] and in one study up to 28 days [16], while persistence on porous surfaces, including cardboard and cotton, is shorter [15,16].…”
Section: Introductionmentioning
confidence: 99%